2009
DOI: 10.4218/etrij.09.0109.0121
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Borrowing Addressing Scheme for ZigBee/IEEE 802.15.4 Wireless Sensor Networks

Abstract: This paper proposes a distributed borrowing addressing (DIBA) scheme to solve problems of failure in address assignments resulting from limited tree depth and width when the distributed address assignment mechanism is used in a ZigBee/IEEE 802.15.4 wireless sensor network. DIBA is a method of borrowing addresses from neighbor nodes for newly entering nodes and assigning the borrowed addresses. Its network or sensing coverage can increase with almost the same overhead as the existing method. DIBA is a simple an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…Authors in this paper have shown the orphanage problem to be NP-complete and suggested some heuristics to deal with it. Another approach to deal with orphanage problem is to allow router nodes to borrow blocks of address space from other nodes having unused addresses [13]. Under the proposed protocol, all router nodes broadcast Available Address Count (AAC) in their beacon frames.…”
Section: Related Workmentioning
confidence: 99%
“…Authors in this paper have shown the orphanage problem to be NP-complete and suggested some heuristics to deal with it. Another approach to deal with orphanage problem is to allow router nodes to borrow blocks of address space from other nodes having unused addresses [13]. Under the proposed protocol, all router nodes broadcast Available Address Count (AAC) in their beacon frames.…”
Section: Related Workmentioning
confidence: 99%
“…In the example of the (Cm, Rm, Lm) = (4, 4, 4) network in Fig. 1, when a new node A cannot enter the network because of Cm limits in DAAM, addresses can be assigned to new nodes by borrowing unused addresses using a method described in [13]; however, it still cannot use all unreserved addresses.…”
Section: Address Assignmentmentioning
confidence: 99%
“…We focus on the distributed addressing in this paper, thus hybrid address assignment (HAA) [12] is compared to the proposed method. In distributed borrowing addressing (DIBA) [13], when a new node cannot enter the network because of topological parameter limits of DAAM, an address can be assigned to the new node by borrowing one of addresses that the neighbor node does not assign yet to its child nodes. This method still cannot use all unreserved addresses like DAAM.…”
Section: Introductionmentioning
confidence: 99%
“…When a new node sends an association request to a router of a ZigBee network and this router does not have any free address, it will ask other neighboring routers to lend an unassigned address to serve the new node. Park et al [8] propose a distributed borrowing addressing scheme (DBAS) by allowing a parent node to borrow a maximum unused address space to alleviate the orphan problem.…”
Section: Introductionmentioning
confidence: 99%
“…We improve the borrowing scheme of [8] by allowing a parent router to borrow a flexible subtree of address space from a neighbor. We also define the detailed procedure for our address-borrowing scheme, which is compatible with the ZigBee standard.…”
Section: Introductionmentioning
confidence: 99%